Critical Discourse Analysis of Wives' Attitudes After Watching the Film "Suara Hati Istri" in the RT 2/RW 3 Ujungbatu Community: Applying Norman Fairclough's Three-Dimensional Model - Nuratika; Asih Ria Ningsih; Rani Zahra; Anisa Fitri (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research aims to examine the impact of television viewing, specifically through the FTV film Suara Hati Istri, on married women in the community of RT 2/RW 3 Ujungbatu, focusing on changes in the way wives treat their husbands. The study adopts a qualitative descriptive approach, utilizing observation as a method to enrich the data collection process. The data analysis is conducted using Norman Fairclough's critical discourse analysis framework, which encompasses three dimensions: Text, Discourse Practice, and Sociocultural Practice. The findings indicate that the viewing activity of wives has significantly increased during the Covid-19 pandemic, leading to changes in their attitudes and behaviors towards their husbands. The influence of the film, as reflected in the discourse and sociocultural context, has contributed to these shifts, with the content of the film reinforcing certain perceptions about marital dynamics, often portraying the wife as a victim and the husband as the source of domestic conflicts. This study highlights the role of media in shaping domestic relationships and the ideological influence exerted through television programs.